Molecular circuits in thrombosis and inflammation - Esmon, Charles T (Thrombosis and haemostasis, 2013)
Inflammatory cytokines promote the activation of coagulation through the induction of tissue factor, downregulation of thrombomodulin and upregulation of plasminogen activator inhibitor. In addition to these mechanisms, infections can trigger the release of extracellular traps from leukocytes consisting of DNA and histones. Tissue injury results in release of nucleosomes. Either of these histone containing structures activate platelets and form a potent procoagulant surface on polyphosphates secreted from the platelets, thereby augmenting thrombus formation. In addition, the histones can inhibit thrombomodulin function. The combination of augmenting the platelet procoagulant activity and impairing thrombomodulin activity probably explains the microvascular thrombotic problems observed when histones are infused into mice. Of the histones, H4 is the most potent in all of these activities. DNAase or blocking histone H4 can decrease the thrombotic response initiated by either the extracellular traps or nucleosomes. In addition to the direct prothrombotic activity of histone-DNA complexes, the complexes trigger activation of the toll-like receptors 2, 4 and 9 thereby increasing inflammatory cytokine formation and fostering thrombotic responses through the mechanisms mentioned previously. Furthermore, these cytokines are likely to increase cell necrosis and apoptosis releasing nucleosomes and further augmenting the activation of leukocytes with the subsequent release of extracellular traps. Blocking this histone-mediated cascade has the potential to impact a variety of clinical conditions including sepsis, trauma, chemical toxicity, transplant injury and reperfusion injury.